Porcine astrovirus type 3 in central nervous system of swine with polioencephalomyelitis - Arruda, Bailey; Arruda, Paulo; Hensch, Melissa; Chen, Qi; Zheng, Ying; Yang, Chenghuai; Gatto, Igor Renan Honorato [UNESP]; Ferreyra, Franco Matias; Gauger, Phil; Schwartz, Kent; Bradner, Laura; Harmon, Karen; et al. (My University, 2017)
Using next-generation sequencing, we identified and genetically characterized a porcine astrovirus type 3 strain found in tissues from the central nervous system of 1 piglet and 3 sows with neurologic signs and nonsuppurative polioencephalomyelitis. Further studies are needed to understand the potential for cross-species transmission and clinical impact.